PELATIHAN PEMANFAATAN LAPORAN KEUANGAN DAN PENGENALAN INVESTASI PADA UMKM PERUMAHAN MUKA KUNING - Dian Efriyenty; Hikmah Hikmah; Risca Azmiana (Glow: Jurnal Pengabdian Kepada Masyarakat, 2023)
The problems found in the field are related to the weak knowledge of MSMEs related to understanding financial statements, lack of expertise based on financial transactions that occur in daily activities. As well as the profits obtained cannot be obtained in any form of investment, so that the impact of the profits they feel is very small. Meanwhile, the level of need for spending often increases. Likewise, MSME actors do not know good financial arrangements, make accounting according to the cycle. Not being able to arrange financial reports as they should, weak knowledge of MSMEs related to finance and investment can make it difficult to control the business they have. The practice method and lecture method are used in financial statement transactions in the form of services, trading and manufacturing companies and the introduction and risk practice of investment banking. The termination of the process in this service activity is that financial business actors record according to the stages. The results of this dedication have been carried out for five meetings with guiding material on financial transactions to ledgers and dissemination of banking investment products.